2023
DOI: 10.1186/s12302-023-00717-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, remobilization and accumulation of organic contaminants by flood events in a meso-scaled catchment system

Abstract: Background Extreme weather events and natural disasters such as floods can cause severe damage and impacts on catchment systems covering natural as well as urban, industrial or agricultural areas. Thus, floods often lead to the acute and unusual release of organic pollutants, as well as the remobilization of legacy contaminations or old burdens. Floodplains are then of major relevance for the accumulation of pollutants. Accordingly, various floodplains distributed throughout the course of the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…The vast destruction in the study area, the flooding of industrial sites, and flushing out of sewage systems all contribute to the release and distribution of DIPNs throughout the river catchments. This is further supported, as Schwanen et al [92]-this issue, have also identified DIPNs in the Rur river into which the Vicht and Inde rivers flow. These downstream observations are likely linked to industrial emission sources along the Vicht and Inde catchments where most of the destructive flood-impacts took place.…”
Section: Urban Effluents and Wastewater Indicatorssupporting
confidence: 59%
See 3 more Smart Citations
“…The vast destruction in the study area, the flooding of industrial sites, and flushing out of sewage systems all contribute to the release and distribution of DIPNs throughout the river catchments. This is further supported, as Schwanen et al [92]-this issue, have also identified DIPNs in the Rur river into which the Vicht and Inde rivers flow. These downstream observations are likely linked to industrial emission sources along the Vicht and Inde catchments where most of the destructive flood-impacts took place.…”
Section: Urban Effluents and Wastewater Indicatorssupporting
confidence: 59%
“…Through the past two decades, few studies provided evidence for the widespread distribution of Mesamoll ® in the environment, as well as the ability to adsorb and accumulate in sediments (e.g., [7,34,36,83,94]). Mesamoll ® pollution in the Rur catchment, to which the Vicht-Inde catchment contributes, has previously been documented by Schwanen et al [92].…”
Section: Urban Effluents and Wastewater Indicatorsmentioning
confidence: 57%
See 2 more Smart Citations
“…In the immediate aftermath of the flooding, when the extensive deposition of flood sediments became apparent, concerns arose due to the possible contamination of the sediments [108]. The exceptionally high water levels caused overflowing in areas usually unaffected by flooding, which activated additional pollution sources, as shown by enhanced pollutant levels in the exceptionally widespread deposited sediments [109,110].…”
Section: The July 2021 Floodingmentioning
confidence: 99%